An Atomic Study of Substructures Formed by Shear Transformation in Cast γ-TiAl - Hanlei Zhang; Hongchao Kou; Xiaolei Li; Bin Tang; Jinshan Li (Advances in Materials Science and Engineering)
Substructures and microsegregation of γ/γ laths are analyzed with HRTEM and HAADF-STEM. Results show that the substructures are generated during evolution of shear transformation on the (111-) plane of γ lath. At the beginning, shear transformation evolves in a single γ lath, and a superstructure intrinsic stacking fault (SISF) forms in the γ lath. After the formation of the SISF, the shear transformation may evolve in two different ways. If the shear transformation evolves into neighboring γ laths, the SISF also penetrates into neighboring γ laths and a ribbon of SISFs forms. If shear transformation continues to evolve in the original lath, complex substructures begin to form in the original. If shear transformation in the original lath is homogeneous and complete, secondary twin forms which may further grow into twin intersection. Incomplete shear transformation could not form secondary twins but generates a high concentration of planar faults on the (111-) plane. These planar faults may further penetrate the γ/γ lath interface, grow into adjacent laths, and form a ribbon of planar faults.